Investigating students needs for TPACK elements in listening materials for an English for economics and business e-book - M Zaim; Vanica Serly; Muhd. Al Hafizh; Nur Rosita; Delvi Wahyuni; Leni Marlina; Muflihatuz Zakiyah (Studies in English Language and Education, 2025)
Developing an English e-book for Economics and Business with sufficient and proper content, pedagogical approaches, and integrated technology is required. This research analyzed Economics and Business faculty students need for TPACK elements of listening materials in an e-book for learning English for Economics and Business. Listening material is highlighted because it is the most challenging skill to acquire among many non-English major students. This needs analysis can provide more focused and practical listening materials in English for Economics and Business, facilitating students acquisition of the necessary abilities to improve their listening skills and for their future careers. Accordingly, descriptive research was conducted, and the questionnaire was used to collect data related to the students needs, which were analyzed from five aspects: target situations, discourse, deficiency, present situations, and TPACK elements (technology, pedagogy, content, technological pedagogy, technological content, pedagogical content, and technological pedagogical content). From an ESP perspective, the data were analyzed descriptively. The study reveals that students require technology such as audio, short clips, and songs with engaging and meaningful listening materials, namely, business ethics, job interviews, business meetings, negotiations, and discussions. This study provides insights for English for Economics and Business e-book authors to design and develop e-books based on students need for TPACK elements for listening materials.